2018
DOI: 10.1002/marc.201800415
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Os(II)‐Based Metallo‐Supramolecular Polymers

Abstract: This work presents the preparation of a series of novel Os(II)-based metallo-supramolecular polymers (polyOss: linear polyOsL1 and hyperbranched polyOsL1 L2 ) that show a broad absorption spanning 312 to 677 nm and a low Os(II)/(III) redox potential of 0.94 V. The electrochromic properties of a polyOs film cast on an ITO substrate is investigated. The change in transmittance (ΔT) of polyOsL1 is 49.9%, and the switching times for coloration (t ) and bleaching (t ) are 0.70 and 0.82 s, respectively. The introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…1,4-Di([2,2 0 :6 0 ,2 00 -terpyridin]-4 0 -yl)benzene has been used as a ligand in the formation of mononuclear complexes (Santoni et al, 2013;Laramé e-Milette & Hanan, 2017), binuclear complexes (Santoni et al, 2013;Schmittel et al,2006;Maekawa et al, 2004), tetranuclear complexes (Schmittel et al, 2005), one-dimensional coordination polymers (Koo et al, 2003), two-dimensional coordination polymers (Bulut et al, 2015;Jones et al (2010), and numerous metallo-supramolecular polymers (without reported crystal structures), see for example: Vaduvescu & Potvin, 2004;Nishimori et al, 2007;Han et al, 2008;Schwarz et al, 2010;Ding et al, 2012;Muronoi et al, 2013;Szczerba et al, 2014;Munzert et al, 2016;Meded et al, 2017;Bera et al, 2018. A search of the Cambridge Structural Database (CSD, Version 5.40, update August 2019; Groom et al, 2016) for the ISSN 2056-9890 title compound yielded only nine hits (see supporting information), which included the report on the structure of the orthorhombic polymorph, Form II, by Fernandes et al (2010).…”
Section: Chemical Contextmentioning
confidence: 99%
“…1,4-Di([2,2 0 :6 0 ,2 00 -terpyridin]-4 0 -yl)benzene has been used as a ligand in the formation of mononuclear complexes (Santoni et al, 2013;Laramé e-Milette & Hanan, 2017), binuclear complexes (Santoni et al, 2013;Schmittel et al,2006;Maekawa et al, 2004), tetranuclear complexes (Schmittel et al, 2005), one-dimensional coordination polymers (Koo et al, 2003), two-dimensional coordination polymers (Bulut et al, 2015;Jones et al (2010), and numerous metallo-supramolecular polymers (without reported crystal structures), see for example: Vaduvescu & Potvin, 2004;Nishimori et al, 2007;Han et al, 2008;Schwarz et al, 2010;Ding et al, 2012;Muronoi et al, 2013;Szczerba et al, 2014;Munzert et al, 2016;Meded et al, 2017;Bera et al, 2018. A search of the Cambridge Structural Database (CSD, Version 5.40, update August 2019; Groom et al, 2016) for the ISSN 2056-9890 title compound yielded only nine hits (see supporting information), which included the report on the structure of the orthorhombic polymorph, Form II, by Fernandes et al (2010).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The inclusion of metal ions into a supramolecular polymer, results in a metallo-supramolecular polymer (MSP) [2]. MSPs are generally synthesized by coordination-driven self-assembly (1:1 complexation) of ditopic organic ligands and metal ions [3][4][5]. Therefore, the hybridization of organic and inorganic moieties in MSPs produces unique features, which allow MSPs to be used in a wide range of applications, such as memory devices, molecular motors, sensors, photovoltaic devices, electrochromic devices, light-emitting diodes, proton conduction, and stimuli-responsive materials [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This tpy shows high binding affinity for metal ions through tpy-M 2+ -tpy connectivity [11]. To date, various metal ions such as Fe, Ru, Os, Ni, Co, Cu, Zn, and Cd have been used to create monometallic MSPs with a linear structure [4,12]. MSPs containing two heterometal ions have drawn much attention in recent years because of their attractive functionalities which are mainly originated from the coupling of heterometallic segments into the MSP chain.…”
Section: Introductionmentioning
confidence: 99%
“…. In addition to EC materials such as metal oxides, conjugated polymers, metal complexes, and aryl‐amine‐based polymers, we found electrochromism of metallo‐supramolecular polymers (MSPs) . Fe(II)‐based MSP (polyFe) has reversible redox properties, large EC contrast, quick response, and high coloration efficiency …”
Section: Introductionmentioning
confidence: 99%
“…Our group reported EC devices with polyFe before. A mixture of polymethylmethacrylate (PMMA), propylene carbonate, LiClO 4 , and acetonitrile was used as the electrolyte in the devices . Thermal stability of EC device is required for the smart window application in the car, but the electrolyte does not have stability at high temperature.…”
Section: Introductionmentioning
confidence: 99%